(untitled) (Cultura Económica, 2019)
We reproduce here the presentation held by Berthold Wald in the International Congress “Josef Pieper and Contemporary Thought”, organized in 2005 by UCA for Josef Pieper’s centennial. In his youth, Pieper was involved in sociology and became interested in subjects regarding the situation of the proletariat and the reconstruction of society. The author shows the political and social thought present in Pieper’s less known works and the synthesis he accomplished through the integration of empirical knowledge with a philosophical foundation of the social order.